Artificial Intelligence Di Marketing - Indra Cahya Firdaus; Agung Wijoyo; Sofyan Mufti Prasetiyo (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Most people in the 4.0 era have now followed the rapid development of technology, so that all aspects of life are dominant using sophisticated technology, practical and online. Many entrepreneurs have shifted their business from conventional to digital, this is also the cause of the shift in shopping trends and the increasing prevalence of onlineshop, marketplace to e-commerce. This is due to the support of people who use technological sophistication to prefer instant online shopping. Without the help or utilization of digital or online marketing, it will certainly be difficult for sellers to build brands and brands to be recognized and can compete in a wide market reach. . This is a great opportunity for SMEs to start earning income by utilizing the internet. By understanding consumers' behavior patterns, preferences, and needs, companies can generate valuable insights that can be used to optimize their marketing strategies. With the help of AI, companies can create personalized and relevant experiences for consumers. Through data analysis and natural language processing, AI can understand consumers' individual preferences and curate content tailored to their interests and needs.